Effect of aluminium powder on kaolin-based geopolymer characteristic and removal of Cu2+ - Putra Jaya, Ramadhansyah; Nurliyana, Ariffin; Mohd Mustafa Al Bakri, Abdullah; Postawa, Przemysław; Shayfull Zamree, Abd Rahim; Mohd Remy Rozainy, Mohd Arif Zainol; Śliwa, Agata; Mohd Firdaus, Omar; Wysłocki, Jerzy J.; Błoch, Katarzyna; Nabiałek, Marcin (MDPI AG, Basel, Switzerland, 2021)
This current work focuses on the synthesis of geopolymer-based adsorbent which uses kaolin as a source material, mixed with alkali solution consisting of 10M NaOH and Na2SiO3 as well as aluminium powder as a foaming agent. The experimental range for the aluminium powder was between 0.6, 0.8, 1.0 and 1.2wt%. The structure, properties and characterization of the geopolymer were examined using X-Ray Diffraction (XRD), Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). Adsorption capacity and porosity were analysed based on various percentages of aluminium powder added. The results indicate that the use of aluminium powder exhibited a better pore size distribution and higher porosity, suggesting a better heavy metal removal. The maximum adsorption capacity of Cu2+ approached approximately 98%. The findings indicate that 0.8% aluminium powder was the optimal aluminium powder content for geopolymer adsorbent. The removal efficiency was affected by pH, adsorbent dosage and contact time. The optimum removal capacity of Cu2+ was obtained at pH 6 with 1.5 g geopolymer adsorbent and 4 h contact time. Therefore, it can be concluded that the increase in porosity increases the adsorption of Cu2+.